Breaking the Sitting Cycle: Albania’s School-Based Movement Revolution (Baltic Journal of Sport and Health Sciences, 2026)
The “Active Classrooms Albania” initiative was launched to reduce sedentary time and promote physical activity among primary school students, addressing rising levels of childhood obesity and physical inactivity. The project was implemented within the framework of the national Schools for Health programme, aligning with Strategic Objective 1.2 of Albania’s Health Promotion Action Plan 2030. The goal was to foster daily movement in classroom settings through short, structured activity breaks, requiring no additional equipment or time outside the curriculum.The project was co-developed in 2022 by the Institute of Public Health, in partnership with the Ministry of Health, the Ministry of Education and Sports, and the Schools for Health initiative. The pilot targeted 10 public schools in Tirana and Durrës, selected for their active involvement in health-promotion activities. Stakeholder workshops involving teachers, public health experts, and child psychologists helped tailor the movement routines to classroom realities.Teachers received training through the project training modules and a practical “Movement Breaks Toolkit”. Activities included stretching, yoga-based breathing, and energy-boosting mini-games, delivered 2–3 times per day during classroom hours. Schools designated a Focal Point to monitor implementation and coordinate between the health and education sectors.Evaluation took place over six months, combining focus group discussions and observational tools. Key outcomes included:·         A 31% increase in daily moderate activity reported by students.·         87% of teachers observed improved focus and participation post-activity breaks.·         No interference with academic delivery was reported, and classroom discipline improved.Feedback indicated strong acceptance from both students and educators.Following successful results, the initiative was scaled to an additional 25 schools during the 2023 academic year. Materials were incorporated into the national “Qendro Aktiv” platform, and recommendations for integrating movement breaks into national curricula have been submitted to the Ministry of Education.Conclusion: The initiative demonstrates that integrating low-cost physical activity breaks into routine education is feasible, effective, and scalable. It enhances student engagement, reduces sedentary behaviour, and promotes cross-sectoral collaboration. The project contributes directly to Albania’s national strategy on non-communicable diseases prevention and can serve as a practical model for other low-resource European settings aiming to implement Schools for Health principles.